Trauma, literatura de testemunho e suicídio : traduções possíveis - Rodrigues, Geisi Mara (2013)
This study investigated the trauma of survivors of major atrocity, such as the extermination of Jews - the Shoah - during World War II, and who narrated their experiences of survival but later committed suicide, highlighting the destinations for the pulsional excess. The investigation follows the trail of the Generalized Theory of Seduction (TSG) of Jean Laplanche. The work starts by relating the traumatic experience and production witness literature in general and it continuous walking to the individual experiences of three survivors who committed suicide or, namely, Primo Levi, Jean Amery and Bruno Bettelheim. The experiences of the Lager's survivors have been marked by intromissive sexuality of the other and by reading the narrative of each author whose we are able to verify in the psychic elaborations of the suffered invasion. In Primo Levi's narrative, we highlight the guilt for survival and obligation to witness on behalf of the dead; in Jean Amery's narrative, we see the invasion of boundaries ego and the suicide as the freedom in front of the intrusion of other; and, finally, in Bettelheim's narrative, we see the suicide as autonomy. At the end, we propose three hypotheses for the suicide survivors: the shutdown that occurs in the narrative, result of the translation process, and it leave the ego vulnerable; the suicide would be an actmessage because of the difficulty in translating; and that the suicide as an enigma for the humanity.